KUFRI LOHIT: A NEW RED SKIN POTATO VARIETY - Luthra, Satish Kumar (Potato Journal, 2023)
ABSTRACT: Kufri Lohit is a red skin, medium maturing, main season, high yielding table potato variety recommended for cultivation in North-Indian plains (Eastern & Central plains). It can also successfully be grown in northern plains to meet the seed potato demands of regions that prefer red skin tubers. It is a clonal selection of a cross between Kufri Kanchan and Kufri Khyati. Its plants are medium tall and vigorous having field resistance to late blight. It produces attractive red coloured, ovoid tubers with shallow eyes, cream flesh, and mealy texture. This variety possesses approximately 18% tuber dry matter content and has very good keeping quality. It is responsive to crop nutrition and yields 36–38 t/ha total tuber yield under optimum crop management.